An Analytical Hierarchy Process-Based Technique for Software Requirements Prioritization - Thamer Ahmad Al-Rawashdeh; Feras Al'Azzeh; Feras Al-Tarawneh (IEEE Access)
Software requirements prioritization is a crucial step in the requirements engineering process. It is applied to define the ordering of specific requirements according to schedule and budget constraints. Many requirements prioritization approaches have been proposed in the literature, but not all have been empirically investigated in real-life settings, cannot be used for all types of projects, and do not provide a hierarchical model for the requirements. Therefore, this study proposes an analytical hierarchy process-based technique to prioritize functional and quality requirements prioritization based on stakeholders’ perspectives. The proposed technique has been demonstrated in the organization’s quality management system and eliminates inconsistencies between business and technical stakeholder valuations. The results indicated that the consistency ratio for hierarchy was acceptable (0.089), thereby confirming the accuracy of the analysis. Notably, the effectiveness requirement (28%) was the highest among the functional and nonfunctional categories in this hierarchy.